Relationship between skin blood flow regulation mechanisms and vascular endothelial growth factor in patients with metabolic syndrome - Smirnova, E.; Shulkina, S.; Loran, E.; Podtaev, S.; Antonova, N. (Clinical hemorheology and microcirculation, 2018)
The focus of this paper is the determination of endothelial dysfunction in patients with metabolic syndrome (MetS) and the establishment of a relationship between the traditional biomarkers of endothelial dysfunction and the vascular tone regulation indices obtained from indirect cold tests in MetS patients. Our investigation was conducted on 30 patients aged 45.5±9 years. The control group comprised 14 healthy subjects aged 48.2±2.4 years. The mechanism of vascular tone regulation was investigated using the wavelet analysis of skin temperature oscillations (WAST). The degrees of microvascular vasoconstriction and vasodilatation were determined during contralateral cold tests in the endothelial (0.02–0.0095 Hz), neurogenic (0.05–0.02 Hz) and myogenic (0.05–0.14 Hz) frequency ranges. In MetS patients, vasoconstriction indices were higher and vasodilatation indices were lower than in the subjects of the control group, which is indicative of disorders in the mechanisms of microvascular tone regulation. These indices correlate with the metabolic parameters and VEGF (vascular endothelial growth factor) levels. The correlation of vasoconstriction and vasodilatation indices with the main factors of the metabolic syndrome testifies that the biological and functional aspects of the endothelial dysfunction are closely related.